2011
DOI: 10.1515/znc-2011-11-1204
|View full text |Cite
|
Sign up to set email alerts
|

Feselol Enhances the Cytotoxicity and DNA Damage Induced by Cisplatin in 5637 Cells

Abstract: Transitional cell carcinoma (TCC), which is the most common type of bladder cancer, shows resistance to chemotherapeutic agents due to the overexpression of drug effl ux pumps. In this study, the effects of feselol, a sesquiterpene coumarin extracted from Ferula badrakema, on cisplatin cytotoxicity were investigated in 5637 cells, a TCC subline. Cell viability and DNA lesion were evaluated by thiazolyl blue tetrazolium bromide and comet assays, respectively. Feselol had no signifi cant cytotoxic effect in 5637… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In a study conducted by Soltani et al [ 67 ], the cytotoxic activities of feselol ( 3 ) on the HCT-116, HeLa, A549, and A2780 cancer cell lines were found to be 28, 35, 26, and 20 µM, respectively. Furthermore, some studies reported that feselol ( 3 ) did not show any cytotoxic activity on the bladder (TCC, 5637), K562, HeLa, and stomach (AGS) cancer cell lines [ 14 , 71 , 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a study conducted by Soltani et al [ 67 ], the cytotoxic activities of feselol ( 3 ) on the HCT-116, HeLa, A549, and A2780 cancer cell lines were found to be 28, 35, 26, and 20 µM, respectively. Furthermore, some studies reported that feselol ( 3 ) did not show any cytotoxic activity on the bladder (TCC, 5637), K562, HeLa, and stomach (AGS) cancer cell lines [ 14 , 71 , 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%